Spontaneous Recovery of Paraplegia Caused by Spinal Epidural Hematoma after Removal of Epidural Catheter - Kouhei Iwashita; Kenji Shigematsu; Kazuo Higa; Keiichi Nitahara (Case Reports in Anesthesiology)
We report a patient who developed paraplegia caused by a spinal epidural hematoma after removal of an epidural catheter, which resolved spontaneously. A 60-year-old woman underwent thoracoscopic partial resection of the left lung under general anesthesia combined with epidural anesthesia. She neither was coagulopathic nor had received anticoagulants. Paraplegia occurred 40 minutes after removal of the epidural catheter on the first postoperative day. Magnetic resonance images revealed a spinal epidural hematoma. Surgery was not required as the paraplegia gradually improved until, within 1 hour, it had completely resolved. Hypoesthesia had completely resolved by the third postoperative day.